The Potential of the Problem Posing Method on Mathematics Learning Outcomes: A Study in Grade IX-G Students of SMPN 244 Jakarta, Indonesia - Purwidi Sumaryanto (Community Medicine and Education Journal, 2023)
Mathematics is still one of the subjects that is less attractive to students. Students often think that mathematics is difficult or even boring. The posing method is one of the efforts that can be developed in order to be a solution in the process of teaching mathematics so that mathematics is no longer something difficult and frightening. A posing method is an approach to learning mathematics where students are not only oriented to solving a problem. However, students participate in making questions. This study aimed to determine the potential of the posing method in improving mathematics learning outcomes in grade IX-G students of SMPN 244 Jakarta, Indonesia. This study is an experimental study with a pre-post test design approach. A total of 36 research subjects participated in this study. The posing method intervention in this study consisted of 2 cycles, with 2 meetings in each cycle. Furthermore, re-intervention and evaluation of the implementation of cycle II as in cycle I. The success of the posing method is carried out by assessing student learning outcomes. Data analysis was carried out in a univariate manner by comparing the average and frequency of student learning outcomes. The results of the study showed that there was a shift in learning outcomes from those that were initially at a score of 5 and then experienced improvement after the posing method was applied to the majority of scores 8 and 9. In conclusion, the posing method has the potential to improve mathematics learning outcomes in grade IX-G students of SMPN 244 Jakarta, Indonesia.